Olap application development for multiple versions query in multidimensional database systems - Jarernsri L. Mitrpanont (2018)
OLAP is an analytical tool necessary for strategic decision support. The analytical query is typically made over a multidimensional database (MDB) or a data warehouse (DW). Thus, the query result reflects the analytical views of structure and content of the underlying database. If there are changes in MDB or DW, the query result will represent the information according to the current database schema and instances. However, the historical data may be needed for an advance decision support analysis such as multi-period of data analysis, trend prediction, and what-if analysis. In this paper, we propose temporal version mapping concept and SQL query rewriting technique that is capable of supporting the OLAP query analysis in multidimensional database systems modeled on multiversion schema. Finally, we present our implementation system prototype as a supporting tool for the analytical queries made on several versions of multidimensional database.